Association between resolved hepatitis B virus infection and depression in American adults : a cross-sectional study - Zihan Qin; Yizhuo Liu; Yifei Liu; Anqi Yang; Ruoyi Zhang; Kun Zhang; Shutian Zhang (Scientific Reports)
Abstract Hepatitis B virus (HBV) infection is a global health concern, and it can potentially affect mental health like depression. Resolved HBV infection, often perceived as a milder form of HBV infection, are often overlooked, and the association between it and depression remains unclear. This study aims to investigate the association between resolved HBV infection and depression. A cross-sectional analysis was conducted using the National Health and Nutrition Examination Survey (NHANES) data from 2005 to 2018, including 20,655 adult Americans. Resolved HBV infection was defined as HBV surface antigen (HBsAg) negative and HBV core antibody (HBcAb) positive. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9) score. Propensity score matching (PSM) was performed to balance baseline characteristics. Algorithms such as inverse probability of treatment weighting (IPTW) were also applied. Among the participants, 1,551 (7.5%) were reported to have resolved HBV infection. Depression was reported by 1,796 participants (8.7%), with a higher prevalence among those with resolved HBV infection (10.6%) compared to those without HBV infection(8.5%). PSM and IPTW revealed a significantly positive association between resolved HBV infection and depression (PSM: OR = 1.40, 95%CI 1.09–1.79, p = 0.008; IPTW: OR = 1.48, 95%CI 1.26–1.74, p < 0.001). Subgroup and sensitivity analyses supported the robustness of the findings. The results suggest a complex relationship between resolved chronic viral infections and mental health. Based on this finding, it is advisable to conduct psychological monitoring and offer support to individuals who have achieved a functional cure for HBV. Further prospective studies are still needed to reveal the potential mechanism.